Effect of Carbonation on Concrete Strength: A Systematic Review - Ramlee, Nur Shafiqah; Juki, Mohd Irwan; Abo Sabah, Saddam Hussein (Recent Trends in Civil Engineering and Built Environment, 2021)
Carbonation of concrete is presence in the concrete mechanism when carbon dioxide comes from air penetrates through pores into concrete and  with calcium hydroxide to form calcium carbonate. Presence of carbon dioxide take lead on reduction of porosity and permeability of the concrete and also cause to the corrosion of reinforced concrete steel. The objective study is to study the effect of carbonation on concrete properties and to study the relationship between carbonation depth and concrete compressive strength. In this study, the systematic literature review had evaluate the objective of the study. Boolean operator that have been used in this method play an important role in a search engine database. Further detail of result and discussion were made based on the comparison of carbonation depth and compressive strength of the concrete from the the result obtained in previous research. From the results and discussion of the study will show the influence of carbonation on concrete strength. The compressive strength of concrete has slightly increases due to present of carbon dioxide and the exceeding water cement ratio influenced the strength of concrete as a result from this study. The presence of carbon dioxide in concrete make compressive strength became increase and also that carbon dioxide reduce the porosity of the concrete moreover with the suitable amount of water effect the presence of carbon dioxide so can be said the higher the water ratio of concrete, the decrease compressive strength of concrete. As recommendation to improve this study, experimental study can be conducted with following the grade of concrete .For further study the variety of duration in carbonation chamber with different concentration of carbon dioxide to see the effect on compressive strength and also duration of curing to 56 days, 91 and 112 days.